The effect of cork removal on the radial growth and phenology of young cork oak trees - Fialho, C.; Lopes, F.; Pereira, H. (Forest Ecology and Management, 2001)
The effect of the removal of cork was studied in 11-years old cork oak trees (Quercus suber L.), growing in favorable conditions, in relation to phenology and radial growth during two years. Longevity of leaves was 14±15 months (1996, 1998) and 10 months (1997). Bud burst started in mid-February and leaf ¯ushing in April, extending until June. Neither a distinct two-period ¯ushing nor an autumn bud burst or leaf ¯ushing were observed. Radial growth started in mid-April and continued until the end of November, with the maximum growth in June and July. In trees with the removal of cork, leaf abscission occurred a little earlier and new branches had on average 23% fewer new leaves. The radial growth of the trees and its general seasonal pattern were not affected by cork removal in the year of removal or in the year after. The only observation was a shift of the maximum radial growth rate from June to July for the trees where cork had been removed
Keywords: cork removal; cork-oak; Phenology; Quercus suber; Radial growth

Characterization of cork growth and quality in one region of production. - Ferreira, A.; Lopes, F.; Pereira, H. (ANNALS OF FOREST SCIENCE, 2000)
Cork growth and quality were characterised in 5 cork oak stands within the production area of the Sado basin (Alcacer do Sal, Portugal) based on a field sampling on 40 trees/stand. Cork thickness was on average 33.8 mm, with 75% of the samples in the commercial classes above 27 mm suitable for production of stoppers. Porosity measured by image analysis was 4.6% on average. Between toe and between stand variability of cork quality was large. The annual average cork growth for a production cycle with 8 complete growth years was 4.1 mm, being highest during the years following cork extraction and decreasing during the cycle. For this region, a production cycle of 9 years is adequate for raw-material industrial requirements. The results show the importance of between tree variability in growth and especially in quality.
The following values have no corresponding Zotero field: pub-location: 23 RUE LINOIS, 75724 PARIS CEDEX 15, FRANCE publisher: EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER
Keywords: Cork; Growth; Porosity; Quality; variability